Impact of Climate Change on Agriculture in Nepal and Strategies for Farmer Adaptation and Economic Resilience - Shrestha, Prabin; KC, Anup; Karki, Dil Kumari; Shrestha, Nishesh; Bharati, Aakriti; Giri, Suja (Journal of Multidisciplinary Research Advancements, 2024)
This document investigates the impacts of climate change on agriculture in Nepal, a country identified as highly vulnerable to climate-related losses. The study used desktop review to gather relevant literature and thematically present the obtained data. It highlights the crucial challenges farmers face, including decreasing crop yields, declining livestock health, and threats to food security due to rising temperatures, altered precipitation patterns, and extreme weather events such as floods and droughts. The study utilizes data from climate risk assessments, including the "Global Climate Risk Index 2021" and recent findings on glacial lake outburst floods (GLOFs), to underscore the urgency of adaptation strategies for agricultural resilience. The document emphasizes that even marginal changes in temperature and precipitation can significantly affect agricultural productivity, supported by analyses of historical data and regional studies on temperature trends. It shows the need for adaptation strategies that consider unique regional vulnerabilities and the socio-economic conditions of farmers in Nepal.